Synthesis, Characterization and Antimicrobial Activity of Transition Metal Complexes of Hydrozone of Isonicotinic Acid Hydrazide - Syed Tajudeen*, S.; Dastageer, M.S. (Asian Journal of Chemistry, 2010)
The transition metal complexes of hydrazone of isonicotinicacid hydrazide, viz., 1NH-AP of the type M-3(1NH-AP)(M = Mn, Fe, Co, Ni, Cu and Zn) have been synthesized andcharacterized by infrared and magnetic susceptibility measurementsand probable structures assigned to them.